Strategic Leadership for Technological Evolution in Diniyah Madrasah Education: Optimizing Development with Mechanical Advancements - Ahmad Rafi'i; Sapuding, Baiyeenah (Al-Qalam Institue, 2023)
This study aimed to describe the concept of leadership in realizing the mechanical development of Madrasah Diniyah. The method used qualitative-descriptive. Data was collected through observation and interviews with the head of the madrasah, diniyah, the Deputy Head of Curriculum, and subject teachers. Data analysis involves condensing data, presenting data, and drawing conclusions. The results showed that the madrasa's principal initiated two construction patterns in education development at Madrasa Diniyah Takmiliyah Mambaul Ulum. First, the construction of the organizational structure as educational development from a structural point of view of the madrasah diniyah organization, and Second, the construction of the curriculum as educational development from a functional view of madrasah diniyah. The construction concept used by the head of Madrasah Diniyah Takmiliyah Mambaul Ulum can develop Madrasah Diniyah education. It can be seen from graduates who can develop and instil three important aspects (cognitive, affective, and psychomotor) in themselves from learning experience and habituation. The leadership construction of the head of Madrasah Diniyah Takmiliyah Mambaul Ulum was also outstanding and strengthened the mechanical structure of educational institutions structurally and functionally.